Hepatocyte homeostasis for chromosome ploidization and liver function is regulated by Ssu72 protein phosphatase. Issue 1 (26th November 2015) - Kim, Se‐Hyuk; Jeon, Yoon; Kim, Hyun‐Soo; Lee, Jin‐Kwan; Lim, Han Jeong; Kang, Donglim; Cho, Hyeseong; Park, Cheol‐Keun; Lee, Ho; Lee, Chang‐Woo
Abstract : Hepatocyte chromosome polyploidization is an important feature of liver development and seems to be required for response to liver stress and injury signals. However, the question of how polyploidization can be tightly regulated in liver growth remains to be answered. Using a conditional knockout mouse model, liver‐specific depletion of Ssu72 protein phosphatase was found to result in impairment in regulation of polyploidization. Interestingly, the aberrant polyploidization in Ssu72‐depleted mice was associated with impaired liver damage response and increased markers of liver injury and seemed to mimic the phenotypic features of liver diseases such as fibrosis, steatosis, and steatohepatitis. In addition, depletion of Ssu72 caused deregulation of cell cycle progression by overriding the restriction point of the cell cycle and aberrantly promoting DNA endoreplication through G2 /M arrest. Conclusion : Ssu72 plays a substantial role in the maintenance of hepatic chromosome homeostasis and would allow monitoring of liver function. (Hepatology 2016;63:247–259)